Inpatient dermatology: Pattern of admissions and patients' characteristics in an Australian hospital. (29th August 2013) - Bale, Jessica; Chee, Paul
Abstract Objectives To report the pattern of dermatology admissions and inpatient characteristics at a tertiary Australian hospital and compare the data with international studies. Methods The study was conducted at a tertiary referral hospital in New South Wales, Australia. Clinical databases were searched retrospectively to include all inpatient admissions under dermatology from 1 January to 31 December 2011. The medical records were reviewed to gather data on age, sex, ethnicity, length of stay, referral and follow‐up source, diagnosis and other consultations obtained during the admission. Results In all, 97 patients were admitted during the 12‐month period, of whom 44% were female and 56% male. The most frequent reasons for admission were dermatitis or eczema and ulcers. The average length of stay was 10 days, with a median of 5 days. A total of 80% of patients had a stay duration of 10 days or less, and 6% were in hospital for more than 30 days. The diagnosis that accounted for the longest length of stay was ulcers. A large proportion of patients required consultation from another medical specialty during their admission with 91 specialist consultations taking place for the study group. Conclusions Inpatient treatment plays a fundamental role in the management of complex and severe dermatological disease and comparison of these results to future studies in other dermatology units around Australia and internationally may be a valuable area of further work.